Harnessing cGAS–STING axis for therapeutic benefits in systemic lupus erythematosus - Chang, Liu (International journal of rheumatic diseases, 2024)
The cyclic GMP–AMP synthase (cGAS), a prominent intracellular DNA sensor in mammalian cells, controls the innate immune response and the stimulator of interferon genes (STING)‐mediated synthesis of pro‐inflammatory cytokines, such as type‐I interferon (IFN‐I). For decades, IFN‐I has been hypothesized to be essential in the development of systemic lupus erythematosus (SLE), a chronic multisystem autoimmunity characterized by immune complex (IC) deposition in small vessels. Recent findings revealed that the activation of the cGAS–STING pathway by self‐DNA would propagate the autoimmune responses via upregulating IFN‐I production in SLE. In this review, we aimed to provide a comprehensive outlook of the role of the cGAS–STING pathway in SLE pathobiology, as well as, a better understanding of current therapeutic opportunities targeting this axis.